STUDENTS PERCEPTION OF ANKIDROID APPLICATION IN LEARNING ENGLISH VOCABULARY - Seftina, Ayumi; Purnomo, Maslathif Dwi (Universitas PGRI Sumatera Barat, 2025)
This research aims to explore students' perceptions on the use of the AnkiDroid application in English vocabulary learning. Using a descriptive qualitative approach, data were collected through questionnaires given to 30 IX-grade students at a junior high school. The research results show that the majority of students consider AnkiDroid a useful tool for improving vocabulary comprehension. Multimedia features, such as images and sound, were identified as the most helpful elements. Based on the results of this study, to maximize AnkiDroid’s influence, this study recommends enhancing app features, integrating it into school assignments, and increasing teacher involvement. This research highlights the need for stronger support and innovation in educational technology to optimize vocabulary learning outcomes.